Quantifying Ecological Constraints on Motion Signaling - Ramos, Jose A.; Peters, Richard A. (Frontiers in Ecology and Evolution, 2017)
The environment in which animal signals are generated has the potential to affect transmission and reliable detection by receivers. To understand such constraints, it is important to quantify both signals and noise in detail. Investigations of acoustic and color signals now utilize established methods, but quantifying motion-based visual signals and noise remains rudimentary. In this paper, we encourage a more complete consideration of motion signaling environments and describe an approach to quantifying signal and noise in detail. Signals are reconstructed in three-dimensions, microhabitats are mapped and the noise environment quantified in a standardized manner. Information on signal and noise is combined to consider signal contrast from multiple viewpoints, and in any of the habitats we map. We illustrate our approach by examining signals and noise for two allopatric populations of the Australian mallee military dragon Ctenophorus fordi. By ‘placing’ signals in different microhabitats we observed similar signal contrast results within populations, but clear differences when considered in microhabitats of the other population. These preliminary results are consistent with the hypothesis that habitat structure has affected display structure in these populations of lizards. Our novel methodology will facilitate the examination of habitat-dependent convergence and divergence in motion signal structure in a variety of taxonomic groups and habitats. Furthermore, we anticipate application of our approach to consider the visual ecology of animals more broadly.